Caffeine Enhances Memory Performance in Young Adults during Their Non-optimal Time of Day - Sherman, Stephanie M.; Buckley, Timothy P.; Baena, Elsa; Ryan, Lee (Frontiers in Psychology, 2016)
Many college students struggle to perform well on exams in the early morning. Although students drink caffeinated beverages to feel more awake, it is unclear whether these actually improve performance. After consuming coffee (caffeinated or decaffeinated), college-age adults completed implicit and explicit memory tasks in the early morning and late afternoon (Experiment 1). During the morning, participants ingesting caffeine demonstrated a striking improvement in explicit memory, but not implicit memory. Caffeine did not alter memory performance in the afternoon. In Experiment 2, participants engaged in cardiovascular exercise in order to examine whether increases in physiological arousal similarly improved memory. Despite clear increases in arousal, exercise did not improve memory performance compared to a stretching control condition. These results suggest that caffeine has a specific benefit for memory during students’ non-optimal time of day – early morning. These findings have real-world implications for students taking morning exams.